Exploring Distance Learning: The Case of Virtual Exchange Program of Kampung Inggris Indonesia and US University for EFL Students - Istighfaroh, Faridatul; Kumalasari, Ana; Septiana, Vita Nugrah (Faculty of Teacher Training and Education, English Department, UNISKA, Kediri, 2025)
Directed to the few numbers of studies in online exchange programs on EFL students, this study purposely investigates about the remote learning between two institutions in Kampung Inggris Pare, Indonesia and a US university. The exploration of this distance learning highlights on the basic motivation of the virtual exchange program with the primary focuses on the learning impulsion between both stakeholders, the pursuit of the virtual exchange program, and the learning outcomes for EFL students affected by the virtual exchange program. Data were gained from the interview, documentation and observation for 6 weeks and were analyzed descriptively. The result of this study unpacks that the main encouragement of both institutions is (a) to construct an international-vibe class, (b) to enhance the EFL students’ cross-cultural understanding and (c) to broaden the intercultural knowledge. The program exertion utilized the SIOP (Sheltered Instruction Observational Protocol) and this country-mile learning brought more implications for the institutions, teachers and EFL students, particularly in confidence of speaking and listening.